1999
DOI: 10.2337/diacare.22.8.1296
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of symptomatic diabetic polyneuropathy with the antioxidant alpha-lipoic acid: a 7-month multicenter randomized controlled trial (ALADIN III Study). ALADIN III Study Group. Alpha-Lipoic Acid in Diabetic Neuropathy.

Abstract: These findings indicate that a 3-week intravenous treatment with alpha-lipoic acid, followed by a 6-month oral treatment, had no effect on neuropathic symptoms distinguishable from placebo to a clinically meaningful degree, possibly due to increasing intercenter variability in symptom scoring during the study. However, this treatment was associated with a favorable effect on neuropathic deficits without causing significant adverse reactions. Long-term trials that focus on neuropathic deficits rather than sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
251
0
30

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(290 citation statements)
references
References 0 publications
7
251
0
30
Order By: Relevance
“…The ALADIN III study showed that a 3-week i.v. treatment with ALA followed by a 6-month oral treatment could not demonstrate a prior specified effect on neuropathic symptoms, but it indicated some clinically meaningful effects on neuropathic deficits in the treatment of ALA (34). However, the Oral Pilot (ORPIL) study, although with a smaller population, showed that oral treatment with 600 mg ALA t.i.d.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The ALADIN III study showed that a 3-week i.v. treatment with ALA followed by a 6-month oral treatment could not demonstrate a prior specified effect on neuropathic symptoms, but it indicated some clinically meaningful effects on neuropathic deficits in the treatment of ALA (34). However, the Oral Pilot (ORPIL) study, although with a smaller population, showed that oral treatment with 600 mg ALA t.i.d.…”
Section: Discussionmentioning
confidence: 94%
“…So ALA should be considered as a good choice among pathogenetically oriented treatments of diabetic neuropathy. As ALA was first used therapeutically in Germany to treat diabetic neuropathy, there have been various controlled clinical trials assessing the efficacy of ALA in treating diabetic neuropathy (12,33,34,35,36,37). The findings of ALADIN study substantiated that i.v.…”
Section: Discussionmentioning
confidence: 96%
“…ALA has been considered to be safe and effective for treatment of symptomatic diabetic polyneuropathy [10,11]. The aim of the present study was to investigate the possible cardioprotective effect of α-lipoic acid in type 1 diabetic children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Other options that limit end organ dysfunctions should also be considered, such as aspirin, blood pressure and lisinopril for kidney, heart, and vasculature protection. Multiple drugs and other compounds have been proposed in reducing or reversing DN, however none have found to be successful in comprehensive reviews, with polyneuropathy with the anti-oxidant alpha-lipoic acid as a prime failed example [47]. Sadly, medical management in peripheral DN is reduced to controlling the underlying illness and managing symptoms.…”
Section: Medical Managementmentioning
confidence: 99%